Applications of single‐cell multi‐omics sequencing in deep understanding of brain diseases. Issue 3 (7th July 2022) - Zhang, Xu; Lu, Ping; Shen, Xiaorong
Abstract: Introduction: The mammalian brain consists of intricate neural networks of millions to billions of highly differentiated and interconnected cells. Single‐cell sequencing (SCS), a newly developed technology, revolutionises our comprehension of the genomic, transcriptomic, proteomic and epigenomic landscapes of cells within the brain. With single‐cell sequencing technology, it's possible to profile brain cell type diversity, to elucidate the specific function, connectivity and state of brain cells and to reveal the neural complexity, functional organisation and dynamics of the brain, which provides novel data sources for exploration of brain development and diseases. Methods: In this review, we described current single‐cell‐based methodologies used for single‐cell sequencing technology, and then summarised recent applications of this cutting‐edge technology in brain research, including cellular heterogeneity, development and disease mechanisms of the brain. Results: Single‐cell sequencing (SCS) has substantially advanced our knowledge of brain functions and diseases by enhancing the resolution of diverse cell subpopulations within the brain, identifying novel gene signatures and cell markers and shedding light upon functional differences and developmental trajectories. Conclusion: Despite a large amount of work remains to be accomplished due to the complexity of the brain and the vast amount of single‐cell data, the prospects of single‐cell sequencing in deciphering brain intricacy and facilitating molecular/clinical/earlier diagnosis, targeted treatment, therapy assessment and prognosis of a wide range of brain diseases are promising. Abstract : Single‐cell sequencing (SCS) revolutionises our understanding of genomic, transcriptomic, proteomic and epigenomic landscapes of cells within the brain. Single‐cell sequencing technologies provide novel data sources available for exploration of brain development and brain‐related diseases. Applications of single‐cell multi‐omics sequencing facilitate brain intricacy deciphering as well as diagnosis, targeted therapy and prognosis of a wide range of brain diseases.